Methodology of Hadith Content Criticism: A Study on the Thought of Salah al-Din bin Ahmad al-Adlabi - Tasmin Tangngareng (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
This article examines Salah al-Din bin Ahmad al-Adlabi’s thought on the subject of methodology of criticism of the Prophet’s hadith content (matan). Al-Adlabi is a hadith scholar who has significat influence on the research methodology of hadith content. In his work entitled Manhaj Naqd al-Matn ‘Inda ‘Ulama al-Hadith al-Nabawiy, al-Adlabi outlines that the background necessitating the importance of the research methodology of hadith content comprises two factors, namely, there have been occurrences of falsification of the Prophet’s hadith at the time of transmission, and there has been a spread of al-wahm, that is, some errors or mistakes in the transmission of the Prophet’s hadith. To determine the quality of a hadith content, al-Adlabi put forward four standards for the validity of hadith content, they are: a), not contradicting to the instructions of al-Qur`an; b), does not conflict with more authentic hadith; c) does not conflict with a healthy mind, senses and history; d) the composition of its statements does not show the characteristics of prophethood. Al-Adlabi’s thought on the methodology of criticism of hadith content obviously worth further discussion. Hence, further study and deeper digging is required in order to give birth to more accurate, constructive, and comprehensive ideas.[Kritik hadis merupakan sesuatu yang penting dalam menilai suatu hadis diterima atau ditolaknya. Kajian atas krtiik hadis terutama kritik sanad sudah banyak dilakukan oleh ulama, sebaliknya kajian atas matan belum banyak. Artikel ini mengkaji Pemikiran Salah al-Din bin Ahmad al-Adlabi tentang Metodologi Kritik Matan Hadis. Al-Adlabi adalah pakar hadis yang memiliki pengaruh yang sangat besar terhadap metodologi penelitian matan hadis. Dalam karyanya yang berjudul Manhaj Naqd al-Matn ‘Inda ‘Ulama al-Hadis al-Nabawiy, al-Adlabi menguraikan bahwa latar belakang pentingnya metodologi penelitian matan hadis disebabkan dua faktor yaitu, telah tersebarnya pemalsuan hadis pada masa periwayatan, dan tersebarnya al-wahm yakni berbagai kekeliruan dalam periwayatan hadis. Untuk menentukan kualitas matan suatu hadis, maka al-Adlabi mengemukakan empat tolok ukur kaedah kesahihan matan hadis, yaitu; tidak bertentangan dengan petunjuk al-Qur`an; tidak bertentangan dengan hadis yang lebih kuat; tidak bertentangan dengan akal yang sehat, indera dan sejarah; susunan pernyatannya tidak menunjukkan ciri-ciri sabda kenabian. Pemikiran al-Adlabi tentang metodologi kritik matan hadis, kelihatannya sangat urgen untuk diperbincangkan lebih lanjut. Oleh karenya, masih diperlukan telaah pemikiran dan perbincangan yang lebih dalam, guna melahirkan ide-ide pemikiran yang lebih akurat, konstruktif, dan komprehensip.]